The Shift of Adjunct Structures of Indonesian Translation of English in a News Portal: A Linguistic Study - Moh Khoirul Anam (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. The purpose of the present study was to explore the phrase that functions as an adjunct in the articles which are written in two version of the language: English and Bahasa Indonesia. Therefore, it can be seen in the deep structure of the article whether the translations are kept to use the same structure from the English or to use another one in the Indonesian translation. This will reveal the strategy that the translator uses in translating the articles. News Articles from www.bbc.com were taken as the data of the present study. In gaining the data, purposive sampling technique was used. This technique was to find out more comprehensive data. There are twenty-two data studied in this study which comprises eleven English and Indonesian text in equal. The data were the same articles that were written in English and their translations, in Bahasa Indonesia. Results of the present study show that, first, there were different variations of constituent constructing the phrase when written in both languages. Second, two different constituents can create a new phrase in which there is no such a head representing the phrase. Third, a preposition in Bahasa Indonesia can precedes the adjectives.Keywords: English, Indonesian, Adjunct, News Portal